Developing India: an intellectual and social history, c. 1930 - 50 - Zachariah, Benjamin (Oxford University Press, 2005)
Historiography of India during 1930-50 period
Includes index - Includes bibliographical references (p. [306]-325)
Keywords: 1930-1950; India -- History -- 20th century -- Historiography; Geschichte; Geschichte 1930-1950; Fortschrittsgedanke; Nationenbildung; Indien